School counselor consultation : skills for working effectively with parents, teachers, and other school personnel - Brigman, Greg, 1951-; Villares, Elizabeth; Mullis, Fran; Webb, Linda DeJong, 1957-; White, Joanna F. (John Wiley & Sons, Inc., 2022)
"The importance of consultation has been discussed for decades. In 1962, Gilbert Wrenn stressed its importance in his book, Counseling in a Changing World. Faust (1968), in his now classic book for elementary school counselors, stated that consultation was more important than either group or individual counseling. Dinkmeyer and Caldwell (1970) recognized consultation as a key component of a developmental guidance program. Over the years, consultation as a counselor intervention has continued to receive support (Dustin & Ehly, 1992; Gysbers & Henderson, 2000; Paisley & McMahon, 2001; Wittmer, 2000). The ASCA National Model: A Framework for School Counseling Programs (2019) includes consultation as a key responsive service critical to the successful implementation of a comprehensive developmental school guidance and counseling program. Writers such as Dinkmeyer, Carlson, and Dinkmeyer (2000) and Myrick (2003) encourage school counselors to consult with adults, because children and adolescents are often powerless to make changes; therefore, it is more useful to work with the significant adults in their lives. Consultation is also time efficient. The counselor can teach the consultee skills that may be applied in similar situations. Thus, more children and adolescents can be reached through consultation than through individual or small group counseling"--